Transformation of pTrcHis and pUC8.2-14 into Escherichia coli BL21 (DE3) - Wan Omar, Wan Siti Atikah; Sulaiman, Ahmad Ziad; Ajit @ Abd Aziz, Azilah; Chisti, Yusuf; Ab Rahim, Mohd Hairul; Leow, Adam Thean Chor (2016)
Recombinant microorganism is a genetically modified microorganism which specifically designed for the expression of target protein production or bioreaction process. As different expression host may contribute to superior results, the transformation of a plasmid carrying the gene of interest into the same strain of competent cells would assist in research assessment. This study focused on the transformation of recombinant lipase from two different sources into Escherichia coli competent cells, BL21 (DE3). The recombinant cells, pUC8.2-14 (American Type Culture Collection (ATCC)®68046™) was harbouring Rhizopus (delemar) oryzae lipase and E. coli Top 10 pTrcHis was harbouring Staphylococcus hyicus lipase, respectively. The transformation is involved preparation of competent cells, polymerase chain reaction (PCR) and DNA sequencing. The DNA sequences obtained was inserted into Basic Local Alignment Search Tool (BLAST), under the databases of National Centre for Biotechnology Information (NCBI), USA. The findings show the respective plasmids were successfully carried by the E. coli BL21 (DE3) for further investigation.